Dynamic Contrast-Enhanced MR with Quantitative Perfusion Analysis of Small Bowel in Vascular Assessment between Inflammatory and Fibrotic Lesions in Crohnʼs Disease: A Feasibility Study - Ippolito, Davide; Lombardi, Sophie; Talei Franzesi, Cammillo; Drago, Silvia Girolama; Querques, Giulia; Casiraghi, Alessandra; Pecorelli, Anna; Riva, Luca; Sironi, Sandro (Contrast Media & Molecular Imaging, 2019)
Aim. To assess the feasibility of dynamic contrast-enhanced perfusion-MRI in characterization of active small-bowel inflammation and chronic mural fibrosis in patients with Crohnʼs disease (CD). Methods. We analyzed a total of 37 (11 women; 23–69 years) patients with known biopsy proven CD, who underwent MR-enterography (MRE) study, performed on a 1.5 T MRI system (Achieva, Philips), using a phased array sense body multicoil, after oral administration of 1.5–2 L of PEG solution. MRE protocol included T1 weighted, SSh T2, sBTFE, and gadolinium-enhanced THRIVE sequences acquired on coronal and axial planes. A dedicated workstation was used to generate perfusion color maps, on which we drown ROI on normal bowel and on pathological segment, thus obtaining related perfusion parameters: relative arterial, venous, and late enhancement (RAE, RVE, and RLE), maximum enhancement (ME), and time to peak (TTP). Results. Quantitative perfusion analysis showed a good correlation with local degree of Crohn’s inflammation activity. Twenty-nine out of 37 patients showed active inflammatory disease (reference standard of active disease: wall bowel thickness and layered enhancement) with following perfusion parameters: REA (%) = 116.1, RVE (%) = 125.3, RLE (%) = 127.1, ME (%) = 1054.7, TTP (sec) = 157. The same parameters calculated in patients with mural fibrosis were as follows: RAE (%): median = 56.4; RVE (%): 81.2; RLE (%): 85.4; ME (%):809.6; TTP (sec): 203.4. A significant difference (p<0.001) between inflamed and fibrotic bowel wall vascularity, regarding all perfusion parameters evaluated, was found, with higher values in active CD localizations. Conclusion. Vascular assessment of perfusion kinetics of bowel wall by dynamic contrast perfusion-MR analysis may represent a complementary diagnostic tool that enables a quantitative evaluation of local inflammation activity in CD patients.